Evolution and Transmission of Cefiderocol-Resistant Acinetobacter baumannii During an Outbreak in the Burn Intensive Care Unit. (17th August 2022) - Smoke, Steven M; Brophy, Alison; Reveron, Samuel; Iovleva, Alina; Kline, Ellen G; Marano, Michael; Miller, Lincoln P; Shields, Ryan K
Abstract: We report on 11 critically ill burn patients treated with cefiderocol for carbapenem-resistant Acinetobacter baumannii infections. Clinical success was achieved in 36% and complicated by treatment-emergent resistance and interpatient transmission of cefiderocol-resistant A. baumannii . Resistant isolates harbored disrupted pirA and piuA genes that were not disrupted among susceptible isolates.